Pharmacological OGG1 inhibition decreases murine allergic airway inflammation - Tanner, Lloyd; Bergwik, Jesper; Bhongir, Ravi K. V.; Pan, Lang; Dong, Caijuan; Wallner, Olov; Kalderén, Christina; Helleday, Thomas; Boldogh, Istvan; Adner, Mikael; Egesten, Arne (Frontiers in Pharmacology, 2022)
Background and aim: Allergic asthma is a complex inflammatory disease involving type 2 innate lymphoid cells, type 2 T helper cells, macrophages, and eosinophils. The disease is characterized by wheezing, dyspnea, coughing, chest tightness and variable airflow limitation for which there is no cure and is symptomatically treated with inhaled corticosteroids and β2-agonists. Molecular mechanisms underlying its complex pathogenesis are not fully understood. However, 8-oxoguanine DNA glycosylase-1 (OGG1), a DNA repair protein may play a central role, as OGG1 deficiency decreases both innate and allergic inflammation. Methods: Using a murine ovalbumin (OVA) model of allergic airway inflammation we assessed the utility of an inhibitor of OGG1 (TH5487) in this disease context. Cytokines and chemokines, promoting immune cell recruitment were measured using a 23-multiplex assay and Western blotting. Additionally, immune cell recruitment to bronchi was measured using flow cytometry. Histological analyses and immunofluorescent staining were used to confirm immune cell influx and goblet cell hyperplasia of the airways. A PCR array was used to assess asthma-related genes in murine lung tissue following TH5487 treatment. Finally, airway hyperresponsiveness was determined using in vivo lung function measurement. Results: In this study, administration of TH5487 to mice with OVA-induced allergic airway inflammation significantly decreased goblet cell hyperplasia and mucus production. TH5487 treatment also decreased levels of activated NF-κB and expression of proinflammatory cytokines and chemokines resulting in significantly lower recruitment of eosinophils and other immune cells to the lungs. Gene expression profiling of asthma and allergy-related proteins after TH5487 treatment revealed differences in several important regulators, including down regulation of Tnfrsf4, Arg1, Ccl12 and Ccl11, and upregulation of the negative regulator of type 2 inflammation, Bcl6. Furthermore, the gene Clca1 was upregulated following TH5487 treatment, which should be explored further due to its ambiguous role in allergic asthma. In addition, the OVA-induced airway hyperresponsiveness was significantly reduced by TH5487 treatment. Conclusion: Taken together, the data presented in this study suggest OGG1 as a clinically relevant pharmacological target for the treatment of allergic inflammation.